Implikasi Kebijakan terhadap Keadilan Perlakuan dalam Pemberian Hak Istimewa kepada Investor Asing di Indonesia - Panji Purboyo; Hulman Panjaitan; Paltiada Saragi (Journal of Mandalika Literature, 2025)
The granting of special privileges to foreign investors in certain sectors has the potential to violate human rights, such as the right to land and the right to a healthy environment. Foreign investors often do not exhibit the same level of concern for the rights of local communities as domestic entrepreneurs. Regulations regarding special privileges for foreign investors in Indonesia are frequently unclear, leading to varied interpretations. This situation creates legal uncertainty and opens up opportunities for abuse. This normative juridical research produced several findings. First, the regulation of special privileges for foreign investors in Indonesia is governed by legislation, particularly Law No. 25 of 2007 on Investment. This law provides various facilities, including special privileges, to foreign investors. However, these regulations are not yet fully effective, raising concerns about legal certainty. This indicates the need for reforms in the legal and investment regulation systems so that Indonesia can become a prime destination for investors.Second, Indonesia has implemented the principles of National Treatment (NT) and Most-Favoured-Nation (MFN) in Law No. 25 of 2007 on Investment. Article 6(1) of the law mandates that the government must provide equal treatment to all investors, regardless of their country of origin, in accordance with applicable regulations. This principle ensures legal fairness through “equal treatment” for all investors, whether domestic or foreign, without discrimination. Thus, the Non-Discrimination Principle has been effectively implemented.